2016
DOI: 10.1515/pjct-2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Efficient method for Knoevenagel condensation in aqueous solution of amino acid ionic liquids (AAILs)

Abstract: This work reports on the use of the amino acid ionic liquids (AAILs) which have been used as catalysts in Knoevenagel condensation of various aldehydes with malononitrile. For research we use tetrabutylammonium ionic liquids based on eight natural amino acids. The reaction was carried out in an aqueous medium. Using water as solvent provided effi cient and simple method of isolation of pure product with high yield. Moreover, amino acid ionic liquid dissolved in water could be reused many times without any loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These results mostly follow the utilization of experimental “green” conditions, such as the use of green solvents (water and ethanol) or none solvent at all; grinding or ball milling as mechanical stirring conditions, low temperature and time values and minimal amount of recoverable catalyst. As reported in Table , chitosan, ionic liquids,, molecular metallic catalyst, the combination of both factors in the form of bromozincate ionic liquids or tungsten immobilized heterogeneous catalysts reach moderate to good TON values in the selective synthesis of 2‐benzylidenemalononitrile at the cost of some green principles, such as, high temperatures or long reaction times. In comparison, the materials synthesized in this work, TTS‐MSN‐Co, TTS‐MSN‐G and TTS‐MNPs, show excellent TON values at room temperature and low reaction times.…”
Section: Resultsmentioning
confidence: 84%
“…These results mostly follow the utilization of experimental “green” conditions, such as the use of green solvents (water and ethanol) or none solvent at all; grinding or ball milling as mechanical stirring conditions, low temperature and time values and minimal amount of recoverable catalyst. As reported in Table , chitosan, ionic liquids,, molecular metallic catalyst, the combination of both factors in the form of bromozincate ionic liquids or tungsten immobilized heterogeneous catalysts reach moderate to good TON values in the selective synthesis of 2‐benzylidenemalononitrile at the cost of some green principles, such as, high temperatures or long reaction times. In comparison, the materials synthesized in this work, TTS‐MSN‐Co, TTS‐MSN‐G and TTS‐MNPs, show excellent TON values at room temperature and low reaction times.…”
Section: Resultsmentioning
confidence: 84%
“…30 Recent studies have shown that transformation of an amino acid into an IL may lead to enhanced catalytic performance due to the role of the amino acid anion in the reaction mechanism. 31 Thus, using amino acids which had shown poor catalytic activity towards the condensation reaction (such as Tyr 3%, His 6%, Leu 9%), resulted in reaction time reductions to 30 minutes and conversions increased to 80-89% when these amino acids were incorporated as ILs. 31 In the Knoevenagel condensation, AAILs possessing an anionic amino acid moiety and bound with tetrabutylammonium 31 and cholinium cations, 32 or possessing a cation with an amino acid amide anion 33 were investigated and served as easily separable and recyclable catalysts and solvents/co-solvents.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…31 Thus, using amino acids which had shown poor catalytic activity towards the condensation reaction (such as Tyr 3%, His 6%, Leu 9%), resulted in reaction time reductions to 30 minutes and conversions increased to 80-89% when these amino acids were incorporated as ILs. 31 In the Knoevenagel condensation, AAILs possessing an anionic amino acid moiety and bound with tetrabutylammonium 31 and cholinium cations, 32 or possessing a cation with an amino acid amide anion 33 were investigated and served as easily separable and recyclable catalysts and solvents/co-solvents. The catalytic performance of the carbohydrate AAILs was tested in the model reaction of benzaldehyde with malononitrile in water as the solvent/co-solvent.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Amino acid ionic liquids (AAILs) were utilized recently in many aspects of scientific and technological fields as lubricants, [ 41 ] metal Scavenging, [ 42 ] ligand‐exchange chiral separations, [ 43 ] CO 2 absorbants, [ 44 ] and self‐assembly media of amphiphiles. [ 45 ] The catalytic efficacy of some AAILs observed in the Morita–Baylis–Hillman reaction, [ 46 ] Knoevenagel condensation, [ 47 ] thiol‐Michael addition, [ 48 ] and Baeyer–Villiger oxidation of cyclic ketones. [ 49 ]…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Amino acid ionic liquids (AAILs) were utilized recently in many aspects of scientific and technological fields as lubricants, [41] metal Scavenging, [42] ligandexchange chiral separations, [43] CO 2 absorbants, [44] and self-assembly media of amphiphiles. [45] The catalytic efficacy of some AAILs observed in the Morita-Baylis-Hillman reaction, [46] Knoevenagel condensation, [47] thiol-Michael addition, [48] and Baeyer-Villiger oxidation of cyclic ketones. [49] In following our research preference to design novel nanostructures and investigation of their catalytic activity in heterocycles synthesis, [50][51][52][53][54] herein, we report a novel multi-layered inorganic-organic hybrid gained from silicated titanomagnetite, tryptophan amino acid, and ethyl iodide (nano Fe 3-x Ti x O 4 -SiO 2 @TrpEt 3 + I À ).…”
Section: Introductionmentioning
confidence: 99%